A Study on Properties of Ceiling Board Made from Waste Paper with Urea-Formaldehyde Glue - Hamid N.B.; Ngadiman N.; Kaamin M.; Mokhtar M.; Azmi M.A.M.; Abdullah N.H.; Ramli M.Z. (American Institute of Physics Inc., 2023)
Asbestos and gypsum ceiling board, which recently used, possess certain health risks to humans other than being environmentally-unfriendly. This project aims to investigate the potential use of waste paper in the production of ceiling material to meet the aim of producing an eco-friendly and cost-effective product. The idea of replacing the raw materials to manufacture ceiling boards with the waste paper is to carry out to ascertain its suitability as ceiling board material. The waste paper pulp was sun-dried before mixed with UT adhesive and is compressed under pressure 204 kg/m2 under a temperature of 105C. The tests conducted include density test, moisture content test, and water absorption test. Tabulated results have shown that the material is more lightweight and comparable moisture content compared to the asbestos and gypsum board material. With the same thickness, 500g of waste paper pulp compressed into a mold with a size 450 mm x 450 mm is more suitable to be commercialized. 2022 American Institute of Physics Inc.. All rights reserved.